Handbook of psychophysiology - Cacioppo, John T.; Tassinary, Louis G.; Berntson, Gary G. (Cambridge University Press, 2007)
The Handbook of Psychophysiology, 3rd Edition is an essential reference for students, researchers, and professionals in the behavioral, cognitive, and biological sciences. Psychophysiological methods, paradigms, and theories offer entry to a biological cosmos that does not stop at skin's edge, and this essential reference is designed as a road map for explorers of this cosmos. The scope and coverage in the Handbook have expanded to include both a context for and coverage of the biological bases of cognitive, affective, social, and developmental processes and behavior. In addition to updated coverage of the traditional areas of psychophysiology, coverage of the brain and central nervous system has been expanded to include functional neuroimaging, event related brain potentials, electrophysiological source dipole localization, lesion methods, and transcranial magnetic stimulation. It also includes a section on cellular and humoral systems with attention to the communication across and interactions among cellular, immunological, endocrinological, and neural processes